2011
DOI: 10.4236/health.2011.31004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of exercise habits and physical fitness level on subjective fatigue symptoms in adolescent students

Abstract: This study aimed to examine the influence of exercise habits and physical fitness level on subjective fatigue symptoms (SFS) in adolescent students. Four hundred and one healthy young male adults (age: 16.5 +/- 1.2 yr) participated in the physical fitness test of the Ministry of Education, Culture, Sports, Science and Technology in Japan and responded to the questionnaire on exercise habits and SFS. SFS questionnaire was conducted 6 times with a week interval during the physical fitness test. SFS was compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
(15 reference statements)
0
2
0
1
Order By: Relevance
“…Moreover, undesirable eating habits or poor lifestyle, such as staying up late at night, were associated with the degree of fatigue. Recently, it is reported that fatigue is largely affected by physical fitness level but very little by exercise habits in healthy Japanese adolescents aged 15 -20 years [18]. We have recently reported the fatigue status in 1225 Japanese adolescents aged between 11 and 16 yrs by the questionnaire used in the present study, but the method of data collection was "self-reported" [19].…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, undesirable eating habits or poor lifestyle, such as staying up late at night, were associated with the degree of fatigue. Recently, it is reported that fatigue is largely affected by physical fitness level but very little by exercise habits in healthy Japanese adolescents aged 15 -20 years [18]. We have recently reported the fatigue status in 1225 Japanese adolescents aged between 11 and 16 yrs by the questionnaire used in the present study, but the method of data collection was "self-reported" [19].…”
Section: Discussionmentioning
confidence: 95%
“…Latihan fisik yang terprogram bermanfaat untuk menjaga dan meningkatkan derajat kesehatan dan kesegaran jasmani. 23 Latihan fisik merupakan bagian dari aktivitas fisik yang terencana, terstruktur, serta dilakukan secara berulang-ulang yang bertujuan untuk meningkatkan atau mempertahankan kesegaran jasmani. Latihan fisik yang berulang dan terus menerus akan menimbulkan reaksi biologis berupa penyesuaian diri atau adaptasi dari organorgan tubuh.…”
Section: Journal Of Nutrition College Volume 1 Nomor 1 Tahun 2012unclassified
“…It is conceivable that people with chronic poor lifestyle and exercise habits may more likely complain of fatigue. However, it has been also reported that no clear relationship exists between lifestyle and exercise habits and symptoms of fatigue [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%